A novel pathogenic frameshift variant of CD3E gene in two T-B plus NK plus SCID patients from Turkey - Firtina, Sinem; Ng, Yuk Yin; Ng, Ozden Hatirnaz; Nepesov, Serdar; Yesilbas, Osman; Kilercik, Meltem; Burtecene, Nihan (Springer, 2017)
Severe combined immunodeficiency (SCID) is the most severe form of primary immunodeficiency, which is characterized by the dysfunction and/or absence of T lymphocytes. Early diagnosis of SCID is crucial for overall survival, and if it remains untreated, SCID is often fatal. Next-generation sequencing (NGS) has become a rapid, high-throughput technology, and has already been proven to be beneficial in medical diagnostics. In this study, a targeted NGS panel was developed to identify the genetic variations of SCID by using SmartChip-TE technology, and a novel pathogenic frameshift variant was found in the CD3E gene. Sanger sequencing has confirmed the segregation of the variant among patients. We found a novel deletion in the CD3E gene (NM000733.3:p.L58Hfs*9) in two T-B+ NK+ patients. The variant was not found in the databases of dbSNP, ExAC, and 1000G. One sibling in family I was homozygous and the rest of the family members were heterozygous for this variant. T cell receptor excision circle (TREC) and kappa-deleting recombination excision circle (KREC) analyses were performed for T and B cell maturation. TRECs were not detected in both patients and the KREC copy numbers were similar to the other family members. In addition, heterozygous family members showed decreased TREC levels when compared with the wild-type sibling, indicating that carrying this variant in one allele does not cause immunodeficiency, but does effect T cell proliferation. Here, we report a novel pathogenic frameshift variant in CD3E gene by using targeted NGS panel.
Keywords: Severe Combined İmmunodeficiency; Targeted-Ngs Panel; Cd3e; Trec/Krec Analysis; Severe Combined Immunodeficiency; Recombination Excision Circles; Cell-Receptor; Cd3-Epsilon Gene; Guthrie Cards; Deficiency; Mutations; Quantification; Identification; Expression